Green building technologies in Southeast Asia: A review. (February 2023) - Lai, Fei; Zhou, Jinzhi; Lu, Lin; Hasanuzzaman, M.; Yuan, Yanping
Abstract: The development of green building has been made rapid progress in Southeast Asia due to the contradiction between limited land and increasing population. Owing to the influence of tropical monsoon climate, the buildings in Southeast Asia have the features of high proportion of cooling demand, easy to obtain renewable energy resources, etc. To match the local buildings' special demand, a large number of relevant green building technologies have been developed. Given that the potential of these techniques varies from region to region, their application in the tropics should be examined. Exploring these approaches in detail allows us to rethink how to effectively adapt these techniques to overcome the building energy saving problem in Southeast Asia. This study reviews the characteristics of different existing green building technologies in Southeast Asia and analyzes their application potential. The overview of green buildings, including the definition, development and assessments tools in Southeast Asia is discussed first. And then five aspects of green building envelope, equipment, renewable energy utilization, water conservation, greenery system are reviewed, especially considering the characteristics of climate and resources in Southeast Asia. Existing technology challenges and future outlook are also conducted. Such a comprehensive review is essential for highlighting future research trends in Southeast Asia as well as for identifying the common research streams, thus providing a reference for the development of green building in Southeast Asia.